2016
DOI: 10.1038/oncsis.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolic reprogramming in cancer cells

Abstract: Many human diseases, including metabolic, immune and central nervous system disorders, as well as cancer, are the consequence of an alteration in lipid metabolic enzymes and their pathways. This illustrates the fundamental role played by lipids in maintaining membrane homeostasis and normal function in healthy cells. We reviewed the major lipid dysfunctions occurring during tumor development, as determined using systems biology approaches. In it, we provide detailed insight into the essential roles exerted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
993
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(1,031 citation statements)
references
References 150 publications
(186 reference statements)
30
993
0
8
Order By: Relevance
“…We also observed a significant negative correlation between FF and PE, another recently reported key lipidomic feature of ccRCC associated with tumor growth and proliferation (32). It is important to emphasize that MRI signal is derived from the mobile intracellular lipids (predominantly TG), not from the lipids in the membranes, which are essentially invisible to the Dixon MRI technique.…”
Section: I N I C a L M E D I C I N Esupporting
confidence: 56%
See 1 more Smart Citation
“…We also observed a significant negative correlation between FF and PE, another recently reported key lipidomic feature of ccRCC associated with tumor growth and proliferation (32). It is important to emphasize that MRI signal is derived from the mobile intracellular lipids (predominantly TG), not from the lipids in the membranes, which are essentially invisible to the Dixon MRI technique.…”
Section: I N I C a L M E D I C I N Esupporting
confidence: 56%
“…Hence, Dixon-MRI can be applied to noninvasively predict the abundance and alterations directly in intracellular lipids and indirectly in membrane-bound lipids, which are both linked to ccRCC tumor progression. It has been reported that cancer cells selectively activate cholesterol synthesis pathways to keep up with energy demand and for survival (32,33), and increased activity of lipogenic enzymes such as FASN is a known phenotype in ccRCCs (7,9). Additionally, FASN expression predicts poor prognosis in cancer patients in general (34), and specifically in ccRCC patients (7).…”
Section: I N I C a L M E D I C I N Ementioning
confidence: 99%
“…In line with these data, abundant evidence shows that many tumors grow in the vicinity of adipocytes or metastasize to adipocyterich environments which act as an important reservoir of triglycerides [33]. The hydrolysis of these triglycerides produces free fatty acids used as an energy source by adjacent cancer cells [34,35]. The oxidation of these fatty acids becomes a crucial mechanism on which cancer cells depend to survive in nutrient-and oxygen-depleted environmental conditions [36] such as the hypoxic BMmicroenvironment, suggesting potential for therapeutic strategies aimed to exploit the lipid-related metabolic dependence.…”
Section: Discussionmentioning
confidence: 84%
“…Since then, such changes in the lipid composition of cancer cells have been studied in association with drug resistance. In the 1970s, anti-fungal drugs were revealed to exert synergistic effects with certain chemotherapeutic drugs via altering the membrane lipid composition of cancer cells (22,23), and therapeutic strategies that target lipogenic enzymes have been investigated in preclinical and clinical studies (24). Aberrant activation of AKT is correlated with an increase in lipid raft formation, while the disruption of lipid rafts inhibits AKT activation (25).…”
Section: Repurposing Itraconazole As An Anticancer Agent (Review)mentioning
confidence: 99%